Tuvalu : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
This paper discusses Tuvalu's economic condition, internal happenings, external linkages, and climate. The country has reported slow economic growth after the global crisis. The export and economic expansions have been minimal with many of its goods imported. The main source of income for the country continue to be remittances from its citizens working abroad and donor assistance. The government has laid out a rigid agenda for improving fiscal strength, literacy rate, power, health, and reducing nonpriority expenditure. The authorities believe that these challenges have given a fighting spirit to the country.